1999
DOI: 10.1046/j.1442-2042.1999.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneoscopic treatment of a retrocaval ureter

Abstract: Background: Retroperitoneoscopic surgery was performed on a 41-year-old man with a retrocaval ureter. Methods:The retrocaval segment of the ureter was retroperitoneoscopically separated and the ureter was reanastomosed using an automatic suture device. Results/Discussion: He returned to normal activities four days postoperatively. Postoperative excretory urography showed improvement of hydronephrosis and no residual stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 10 publications
0
24
0
3
Order By: Relevance
“…10,13,18 Other surgeons preferred to place the Double-J ureteral stent in a conventional antegrade manner using a ureteral catheter or guide wire during the procedure. 11,19,[22][23][24] However, earlier the ureteral stent would hinder trimming of the ureter and suture of the posterior anastomosis. 8 Further, if the placement of the Double-J stent was performed in a conventional antegrade manner in LUUS, it could be difficult to place the proximal end of the Double-J stent into the renal pelvis after the ureteral catheter or guide wire was removed.…”
Section: Laparoscopic Ureteroureterostomy For Retrocaval Ureter 805mentioning
confidence: 99%
“…10,13,18 Other surgeons preferred to place the Double-J ureteral stent in a conventional antegrade manner using a ureteral catheter or guide wire during the procedure. 11,19,[22][23][24] However, earlier the ureteral stent would hinder trimming of the ureter and suture of the posterior anastomosis. 8 Further, if the placement of the Double-J stent was performed in a conventional antegrade manner in LUUS, it could be difficult to place the proximal end of the Double-J stent into the renal pelvis after the ureteral catheter or guide wire was removed.…”
Section: Laparoscopic Ureteroureterostomy For Retrocaval Ureter 805mentioning
confidence: 99%
“…Simforoosh et al 21 have reported simultaneous treatment of renal stone and retrocaval ureter with laparoscopic technique. Mugiya et al 22 reported a case, in which retrocaval ureter and upper ureteric calculus were managed during the same procedure. Similarly, Singh et al 23 also described simultaneous management of retrocaval ureter and renal stone by dismembered pyeloplasty and pyelolithotomy.…”
Section: Discussionmentioning
confidence: 99%
“…L'incidence démontrée de l'uretère rétrocave est de 0,9-2 sur 1000 cas, étant 2,8 à 4 fois plus fréquente chez la population male, ce qui a été également confirmé dans notre série [8,9].…”
Section: Discussionunclassified
“…Il y a peu de temps, le TC était considéré comme étant la méthode la plus efficace et minimalement invasive qui permettait de confirmer le diagnostic de l'uretère rétrocave, car elle peut définir les rapports tridimensionnels des structures rétropéritonéales [9]. Elle est particulièrement utile lorsqu'elle est combinée avec la radiorénographie sous diurétiques [17].…”
Section: Discussionunclassified
See 1 more Smart Citation